Analisis Laporan Keuangan Untuk Menilai Kinerja Keuangan pada PT. United Tractors, TBk - Isna Ainul Mafariha; Laella Puspita Sari; M. Thoha Najib (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2024)
This study deals with the analysis of liquidity ratios, solvency, activity and profitability. The aim of this research is to determine the conditions and performance based on financial ratios. The data used are primary data and secondary data. The nature of the research is a quantitative, descriptive research that aims to find factual information. The objects used in this study are financial reports in the form of balance sheets and loss reports of PT. United Tractors, Tbk from 2022 to 2023. The data analysis method used is a quantitative data analysis method. The results of this research are that the solvency ratio and activity ratio from 2022 to 2023 are not good. Looking at the activity coefficient, it can be said that the level of effectiveness based on the inventory turn over from 2022 to 2023 is less effective in carrying out operational activities.